Sandization: climatic dynamics, erosive-depositional, land uses and land cover in the Brazilian Pampa at present - Gomes, Tania Cristina; Verdum, Roberto; Laurent, François; Silva, Neemias Lopes (Sociedade & Natureza, 2022)
In the western part of the Rio Grande do Sul state - Brazil, there are sand spots (called areais) embedded in the Brazilian Pampa landscape. These sand spots, which are associated with unstable and/or stable aeolian deposits, are a legacy of drier climates from the past rather than the present one. Therefore, they provide important paleoclimatic evidence for understanding the evolution of this landscape. Currently, the sand deposits, which had their genesis in dry climates, are subject, at the same time, to wind action in the dry seasons, and surface and subsurface erosion in the rainy season, which remobilizes the unconsolidated sediments, initiating the sandization process and the formation of sand spots. In this study, we propose to identify, classify, and map these aeolian paleofeatures (stable aeolian deposits and sandstones), to understand their erosional and depositional dynamics, and to evaluate the contexts of evolution and agricultural pressure of grazing and monoculture systems in the study area, which characterize the Pampa. It can be stated that the stable aeolian deposits exhibit forms remodeled by pluvial and fluvial erosions, still presenting different degrees of morphological preservation concerning those of the recent past, which is why the present hills can be associated with Holocene longitudinal dune fields. As for agricultural dynamics, the conversion of these hills, mainly from pastureland, used for grazing, into tree and grain monocultures has intensified the pressure on water resources, herbaceous vegetation, and soils (Quartz Neosols), which are particularly sensitive to water and wind erosion.